2017
DOI: 10.1016/j.ultrasmedbio.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Hepatic Microcirculation in Rabbits After Liver Ischemia-Reperfusion Injury Using Contrast-Enhanced Ultrasound

Abstract: Previous studies have shown that contrast-enhanced ultrasound (CEUS) can be used quantitatively to analyze microcirculation blood perfusion in hepatocellular carcinoma patients. However, limited data have described the application of CEUS in hepatic microcirculation after liver ischemic-reperfusion injury (IRI). The purpose of this study was to explore the use of CEUS quantitatively to assess liver microcirculation after liver IRI. We randomly sorted 45 New Zealand rabbits into 3 groups (15 in each). Group A w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…After the HBD of rat loses the blood supply of the hepatic artery, the normal physiological function of the HBD can be guaranteed if the blood oxygen content of the portal vein reaches a compensable level. In this study, it was confirmed that excessive liver tissue ischemia could inhibit the damage of the HBD, and HAL alone was not enough to induce ischemia of the rat HBD (15).…”
Section: Vegfbmentioning
confidence: 62%
“…After the HBD of rat loses the blood supply of the hepatic artery, the normal physiological function of the HBD can be guaranteed if the blood oxygen content of the portal vein reaches a compensable level. In this study, it was confirmed that excessive liver tissue ischemia could inhibit the damage of the HBD, and HAL alone was not enough to induce ischemia of the rat HBD (15).…”
Section: Vegfbmentioning
confidence: 62%
“…To validate the data weighting matrix W d , three methods are used in our algorithm separately. Method 1 is not using W d , Method 2 is using the W d according to Li et al (2017), and Method 3 is using the W d proposed in this study. Figure 5 displays the variation of s1 as a function of the total number of iterations when using these methods in the default experiment (denser division with 5% Gaussian random noise).…”
Section: The Impacts Of the Data Weighting Matrix And The Self-adapti...mentioning
confidence: 98%
“…the first term is the data misfit term and the second term is the regularization term; μ is the regularization parameter and will be introduced in Section 2.2.3. φ d is the fitting error between the observed data and the predicted data from forward modeling. A data weighting matrix W d is constructed based on Li et al (2017) and introduced here to deal with the case that fitting degree for gravity and different components of gravity gradient have large differences:…”
Section: Joint Inversion Using Sl0 Regularization 221 Construction Of...mentioning
confidence: 99%
“…Color Doppler flow imaging and contrastenhanced ultrasound (CEUS) can display changes in hepatic blood vessels and the microcirculation. 6 In this study, the hemodynamic and microcirculation changes during hepatic IRI in rats were compared by color Doppler flow imaging and CEUS to observe transient microcirculation disorders. Furthermore, the vasodilator phentolamine (PHT) was used to improve the hemodynamics and microcirculation after hepatic IRI, which may provide a new strategy to reduce tissue and organ damage due to hepatic IRI.…”
mentioning
confidence: 99%
“…Color Doppler flow imaging and contrast‐enhanced ultrasound (CEUS) can display changes in hepatic blood vessels and the microcirculation . In this study, the hemodynamic and microcirculation changes during hepatic IRI in rats were compared by color Doppler flow imaging and CEUS to observe transient microcirculation disorders.…”
mentioning
confidence: 99%